Me ajudem na f por favor
Anexos:
![](https://pt-static.z-dn.net/files/daa/e82a58cb0f0b7aa8b521c550de3670e7.png)
Soluções para a tarefa
Respondido por
0
x - 3 = -y
3x + 2 = y + 3
x = - y + 3 ==> método da substituição
3x - y = 1
3( -y + 3) - y = 1
-3y + 9 - y = 1
-2y = 1 -9
-2y = -8
y = 4
x = -y + 3
x = -4 + 3
x = -1
Perguntas interessantes
História,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Português,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás